National Security A New Strategy for an Era of Change - Freilich Charles D. (New York Oxford University Press, 2018)
In Israeli National Security, Chuck Freilich presents an authoritative analysis of the military, diplomatic, demographic, and societal challenges Israel faces today, to propose a comprehensive and long-term Israeli national security strategy. The heart of the new strategy places greater emphasis on restraint, defense, and diplomacy as means of addressing the challenges Israel faces, along with the military capacity to deter and, if necessary, defeat Israel's adversaries, while also maintaining the resolve of its society. By bringing Israel's most critical debates about the Palestinians, demography, Iran, Hezbollah, Hamas, US relations and nuclear strategy into sharp focus, the strategy Freilich proposes addresses the primary challenges Israel must address in order to chart its national course.
Includes bibliographical references (pages 431-447) and index.
Keywords: National security--Israel.